Pengabdian Masyarakat Msib6: Optimalisasi Program Kalimasada Pendamping Layanan Administrasi Kependudukan Di Kelurahan Rangkah Kota Surabaya - Yessi Rachmawati; Ni Made Ida Pratiwi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The KALIMASADA program is an abbreviation for Adminduk Aware Community Environmental Area. This program is present as one of the efforts made by the Population and Civil Registration Service of the City of Surabaya to increase the awareness of the people of Surabaya City regarding Population Administration. This program is implemented in every sub-district of Surabaya City, supported by the Head of RT/RW, KSH, and MSIB 6 Internship Students as service assistants who go directly to the field (pick up the ball) to provide convenience for the community in managing population administration optimally. By implementing the KALIMASADA program, it is hoped that the public will understand the importance of population administration which is carried out free of charge without any charges. The implementation of the KALIMASADA Jemput Bola adminduk program uses the observation method by observing objects directly during the assignment period in Rangkah Village, Surabaya City. The results of this activity can show that the role of MSIB 6 students as Companion of Population Administration Services has a significant influence in increasing public awareness of the importance of population administration in today's masses. Apart from that, MSIB 6 students also play a very important role for the community in making it easier to manage population administration files. quickly and efficiently